Development of Innovative Chemistry Practicum Based on Multimedia Senior High School Class XI Semester II Integrated Character Education According to the 2013 Curriculum - Herry Purwanto Panjaitan; Ramlan Silaban; Iis Siti Jahro; Wesly Hutabarat; Ida Duma Riris; Ajat Sudrajat; Nurfajriani Nurfajriani (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This study aims to determine the suitability, feasibility, and integration of character and psychomotor in class XI senior high school chemistry practicum guidebooks used in schools with BSNP criteria. This study is a research and development model modified from the Borg & Gall model. In this study, there are 5 stages carried out; The needs analysis stage, the development stage, the validation stage, the revision stage and the product trial. This research trial was conducted at the Satrya Budi Perdagangan private high school, Simalungun regency. The sample in this study was taken by using cluster random sampling technique. Data collection techniques used BSNP questionnaires, test instrument sheets, character assessment observation sheets, and psychomotor assessment observation sheets. Research result; (2) The innovative chemistry lab guide based on multimedia for class XI Semester II is integrated with character education according to The 2013 curriculum is included in the valid and feasible category for use on average (3) The practicum guide developed can develop the character education values of students, this can be seen from the increase in the attitude value of students before and after using an innovative chemistry-based practical guide multimedia class XI senior high school Semester II integrated character education according to the 2013 curriculum. (4) There are differences in the learning outcomes of students who use an innovative chemistry practicum guide based on multimedia high school grade XI Semester II integrated character education according to the 2013 curriculum with students who use a chemistry lab guide for students with sig. < α (0.000 < 0.05) (5) There are differences in the attitude (character) and psychomotor (skills) values of students who use innovative chemistry lab guides based on multimedia high school grade XI Semester II integrated character education according to the 2013 curriculum with students using chemistry lab guide guide for students.